Intestinal polyparasitism with special emphasis to soil-transmitted helminths among residents around Gilgel Gibe Dam, Southwest Ethiopia: a community based survey - Mekonnen, Zeleke (BMC Public Health, 2016)
BACKGROUND: One third of the world population is estimated to be infected with intestinal parasites. The most affected people are children and the poor people living in tropics and subtropics. Polyparasitism (the concurrent infection with multiple intestinal parasite species) is found to be the norm among the same population although accurate estimate of its magnitude is unknown. It was found that polyparasitism might have a greater impact on morbidity than single species infection which might also increase susceptibility to other infections. Therefore, this study aimed at determining the prevalence and distribution of intestinal polyparasitism with special emphasis on Soil-Transmitted Helminths (STH) among residents around Gilgel Gibe dam located in Jimma zone of Oromia regional state, Ethiopia. METHODS: A total of 1,021 participants were recruited in this study and provided stool samples for parasitological examination. Direct wet mount and Kato-Katz techniques were employed for stool examination. Pearson chi-square test was employed to assess the association of infection status and polyparasitism with gender and age group of the study participants. RESULTS: Five hundred thirty two individuals were infected with at least one parasite, providing the overall prevalence of 52.1%. Among positive individuals, 405 (76.1%), 114 (21.4%), and 13 (2.5%) individuals were infected with only one, two and three species of parasites, respectively. The overall prevalence of intestinal polyparasitism observed among the study participants was 12.4% (127/1,021). The predominant STH was hookworm, with a prevalence of 44.1%. Hookworm and Ascaris lumbricoides were the most frequently recorded combination in cases of polyparasitic infection. The study revealed that there was no significant difference in the distribution of polyparasitism with regard to age group and sex of the study participants (p > 0.05). CONCLUSION: The study indicated the presence of high prevalence of parasites as well as distribution of polyparasitism in the area. Moreover, the detection of Schistosoma mansoni in the community living within close proximity of the newly constructed dam would be taken as an indication of future risk factor. Further investigation on the predictors of polyparasitism and the assessment of effects of polyparasitism on the population are needed. Finally, there is a need to undertake integrated control strategies which involve improved sanitation, health education and chemotherapy that targets the whole community instead of only certain segments of populations.